Synergic interaction between ascorbic acid and antibiotics against Pseudomonas aeruginosa - Cursino,Luciana (2005)
Studies were carried out on in vitro combination of ascorbic acid (AA) with six antibiotics against 12 multi-resistant Pseudomonas aeruginosa isolates. Synergic activity was detected with AA chloramphenicol, kanamycin, streptomycin and tetracycline. Indifference was observed to any antibiotics and antagonism only for chloramphenicol. Results indicated that multiresistant P. aeruginosa was affected by combination of AA and antibiotics. Future research on ascorbic acid-antimicrobial interactions may find new methods to control strains of multiresistant P. aeruginosa.